Engaging Musical Practices: A Sourcebook for Instrumental Music - Burton, Suzanne L.; Snell, Alden H. (Rowman & Littlefield Publishers, 2015)
Engaging Musical Practices: A Sourcebook for Instrumental Music is a long awaited compilation of best practices for instrumental music education. This unique book contains practical and pedagogically oriented chapters written by leaders in the field of instrumental music education. Designed for instrumental music teachers or for use in instrumental methods courses, the book covers a wide range of topics, such as: student readiness for instrumental music beginning an instrumental music program teaching instrumental music at the intermediate and advanced levels working with strings and orchestras motivating students incorporating improvisation into the curriculum selecting repertoire based on curricular goals engaging students in assessment marching band pedagogy and techniques integrating technology considering “traditional” instrumental music practice becoming an instrumental music teacher communicating effectively with stakeholders Contributions by James Ancona and Heidi Sarver, Kimberly Ackney and Colleen Conway, Christopher Azzara, William Bauer and Rick Dammers, Brian Bersh, Suzanne Burton & Rick Townsend, Patricia Campbell and Lee Higgins, Robert Gardner, Richard Grunow, Mike Hewitt and Bret Smith, Dan Isbell, Nate Kruse, Chad Nicholson, Alden Snell, and David Stringham.